Mixed Connective Tissue Disease- A Rare and Distinct Rheumatological Case Study (KYAMC Journal, 2017)
In this article we present this 35 year old lady with history of fever, multiple joints pain with swelling and skin conditions such as tightening, glistening and bluish discoloration while exposure to cold. After taking detailed history and clinical examinations, she was found to have features consistent with multiple rheumatological conditions such as systemic lupus erythematosus and systemic sclerosis. With directed and specific investigation she was diagnosed to have Mixed Connective Tissue disorder.KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 61-63